Aerodynamics of wind turbines - Hansen, Martin O. L. (Earthscan, 2008)
From the Publisher: Aerodynamics of Wind Turbines is the established essential text for the fundamental solutions to efficient wind turbine design. Now in its second edition, it has been entirely updated and substantially extended to reflect advances in technology, research into rotor aerodynamics and the structural response of the wind turbine structure. Topics covered include increasing mass flow through the turbine, performance at low and high wind speeds, assessment of the extreme conditions under which the turbine will perform and the theory for calculating the lifetime of the turbine. The classical Blade Element Momentum method is also covered, as are eigenmodes and the dynamic behavior of a turbine. The new material includes a description of the effects of the dynamics and how this can be modeled in an aeroelastic code, which is widely used in the design and verification of modern wind turbines. Further, the description of how to calculate the vibration of the whole construction as well as the time varying loads has been substantially updated. This is the essential reference for both engineering students and others with a professional or academic interest in the physics and technologies behind horizontal axis wind turbines.